Positivation in the training of health professionals: disease healers or people's caregivers? (Research, Society and Development, 2021)
In recent decades, advances in research in Neuroscience and Genetics, combined with the consolidation of Psychology as a Science of the Psyche, has provoked a reassessment in the way of understanding the Human Being, leaving a perspective where man would only be a determined biological animal by DNA and neurons to be understood as a complex Being that goes beyond these limits. Although professionals are already being invited to more pragmatic reflections on their daily professional practice, this movement is not perceived in the context of the training of these future professionals, especially in medical courses, even with some efforts to implement a discipline with the theme involving health and spirituality. This scenario creates in the researcher's mind concerns about the reasons that prevent even in the face of effective evidence regarding the intrinsic relationship between health and spirituality, academics continue to be trained for a medicine that aims to heal bodies at the expense of caring for people. This article proposes to guide research to try to answer these and other concerns in order to understand the underlying imagery in the construction and consolidation of this scenario from its historical roots to the barriers faced for the implementation of a training model that meets the current demands. Therefore, it briefly analyzed the historical process of positivization in the training of health professionals in Brazil as “curators” of diseases and not as “caregivers” of people, and to understand the importance of spirituality in therapeutics in all its ins and outs.